2020
DOI: 10.1038/s41598-020-64887-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new sialic acid binding region that regulates Siglec-7

Abstract: Siglec-7 is a human CD33-like siglec, and is localised predominantly on human natural killer (NK) cells and monocytes. Siglec-7 is considered to function as an immunoreceptor in a sialic acid-dependent manner. However, the underlying mechanisms linking sialic acid-binding and function remain unknown. Here, to gain new insights into the ligand-binding properties of Siglec-7, we carried out in silico analysis and site-directed mutagenesis, and found a new sialic acid-binding region (site 2 containing R67) in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…Recently, we demonstrated the presence of a secondary Siglec-7 binding site (site 2) in addition to the previously known binding site (site 1) ( 19 ). It has been suggested that Siglec-7 has several Sia-binding sites and that its counter-receptor for Siglec-7 has polyvalent glycans ( e.g.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, we demonstrated the presence of a secondary Siglec-7 binding site (site 2) in addition to the previously known binding site (site 1) ( 19 ). It has been suggested that Siglec-7 has several Sia-binding sites and that its counter-receptor for Siglec-7 has polyvalent glycans ( e.g.…”
Section: Discussionmentioning
confidence: 81%
“…1 A ). In addition, the Siglec-7 R124A mutant, in which the Arg residue essential for Sia binding is replaced by Ala ( 18 , 19 , 20 ), showed no binding, indicating that binding occurred with the V-set domain of Siglec-7. The binding signal of Siglec-7 to K562 was stronger than that of HeLa cells, indicating that K562 expressed the ligands at a higher level than HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Siglec-sialoglycan binding is weak and transient (24). Interaction between Siglecs with multivalent ligands leads to Siglec clustering, which increases the strength of Siglec-ligand binding and initiates cellular signaling (22,(25)(26)(27).…”
Section: Siglec Clustering Enhances Their Signaling Activitymentioning
confidence: 99%
“…The binding domain of Siglec-7 is well characterized, and different crystal structures are available that can help to understand the binding specificity and to identify possible substrates and inhibitors [ 72 , 73 ]. In addition to the sialic acid-binding site around the essential arginine residue (R124), Siglec-7 has another binding site in the V-set domain, and both binding sites contribute to glycan recognition [ 74 ]. The signaling of Siglec-7 is similar to other inhibitory Siglecs, and is mediated through the membrane-proximal ITIM.…”
Section: Sialic Acid-binding Receptors On Nk Cellsmentioning
confidence: 99%